INTEREST RATES, FISHER EFFECT AND ECONOMIC DEVELOPMENT IN TURKEY, 1989-2011 - GÜRİŞ, SELAHATTİN; ÜN, TURGUT (My University, 2016)
This paper investigates the validity of the Fisher Hypothesis in Turkey coveringthe period 2003 – 2012. To test validity of Fisher Hypothesis, this paper uses anAutoregressive Distributed Lag test for threshold cointegration recently introduced in theliterature by Li and Lee (2010). The empirical results which are obtained from this paperindicate that Fisher hypothesis is valid for Turkey, meaning nominal interest rates wouldbe an important leading indicator for inflation.